ANALYSIS OF SAMPLE WORKS IN PUBLISHED UD METHODS IN TERMS OF FORM, MAKAM, RHYTHM AND COMPOSERS - ÇAKIRER, Serdar (Atlas Journal, 2021)
In this study, it is aimed to be examined the methods written and pulished for lute in Turkey in terms of maqam, form, rhythm and composers. The research is a qualitative research and it was conducted in accordance with the document review model. Oud methods in Turkey constitute the universe of the study. The oud methods written by Ali SALAHİ, Sevgican GÜNGÖR, Gülçin Yahya KAÇAR, Mutlu TORUN, Onur AKDOĞU and Şerif Muhittin TARGAN in Turkey, constitutes the sample of the research. Findings, collection of sample works, form and mode structures of sample works and composers were determined and classified. The research is important in terms of whether the sample works used in the methods are suitable for the content of the method written, determining their similar or different aspects and shedding light on the method studies to be made for this instrument. As a result of this research, it has been concluded that there are sample works in each method and that there are differences in terms of makam form and composers of these works.